Male mice emit distinct ultrasonic vocalizations when the female leaves the social interaction arena - Yang, Mu; Loureiro, Darren; Kalikhman, David; Crawley, Jacqueline N. (Frontiers in Behavioral Neuroscience, 2013)
Adult male mice emit large number of complex ultrasonic vocalizations (USVs) when interacting with adult females. Call numbers and call categories differ greatly among inbred mouse strains. Little is known about USV emissions when the social partner departs. To investigate whether call repertoires and call rates are different when the male is interacting with a female and after the removal of the female, we designed a novel male-female social interaction test in which vocalizations were recorded across three phases. During phase 1, the male subject freely interacts with an unfamiliar estrus female mouse in a clean cage for 5 minutes. During phase 2, the female is removed while the male remains in the cage for 3 minutes. During phase 3, the same female is returned to the cage to rejoin the male subject mouse for 3 minutes. C57BL/6J (B6), FVB.129P2-Pde6b(+) Tyr(c-ch)/Ant (FVB), and BTBR T+ tf/J (BTBR) male subject mice were tested in this paradigm. All three strains emitted USVs during the absence of the estrous female, although at lower rates. When the female was reintroduced in phase 3, numbers of USVs were similar to the initial introductory phase 1. Strain comparisons indicated fewer calls in pairs of BTBR males and stimulus females than in pairs of B6 males and stimulus females and pairs of FVB males and stimulus females. In the absence of the female, all FVB males vocalized, while only one third of B6 males and one third of BTBR males vocalized. In all three strains, changes in call repertoires were detected after the female was removed. Call categories reverted to the phase 1 pattern when the female was returned in phase 3. Present findings indicate that males of commonly used inbred strains emit USVs when a partner female leaves the testing arena, suggesting that removing a salient social stimulus may be a unique approach to elicit USVs from mice. Our three-phase paradigm may also be useful for studying attention to social cues, and qualitative differences in